A tunable self-healing ionic hydrogel with microscopic homogeneous conductivity as a cardiac patch for myocardial infarction repair. (June 2021) - Song, Xiaoping; Wang, Xiaorui; Zhang, Jie; Shen, Si; Yin, Wenming; Ye, Genlan; Wang, Leyu; Hou, Honghao; Qiu, Xiaozhong
Abstract: Conductive hydrogel is a potential therapeutic tool to treat damaged heart muscles in myocardial infarction (MI). However, it is still a quite challenge to optimize the fabrication of a therapeutic hydrogel patch that sustains favorable biocompatibility, electronic and mechanical stability under a complicated MI microenvironment. Herein, a tunable self-healing ionic hydrogel (POG1 ) was developed through the introduction of a biocompatible polyacrylic acid (PAA, FDA-approved) into the hydrogel matrix. The fabricated POG1 hydrogel possessed suitable stretchable (>500% strain) and compressive (>85% strain) properties, comparable modulus with mammalian heart (30–500 kPa, Young's modulus), self-healable, and highly stable conductivity during large deformations (~50% compress strain, ~150% tensile strain). Specifically, the established PAA nano-channels inside of POG1 endowed the hydrogel with microscopic ultra-homogeneous conductivity. Compared to those seeded in the electronic conductors-embedded (PPy, CNT, rGO) hydrogels, the cardiomyocytes (CMs) seeded in the POG1 hydrogel exhibited more significantly oriented sarcomeres. This POG1 engineered cardiac patch (ECP) also exerted robust benefits in attenuating left ventricular remodeling and restoring heart function after implantation in vivo . This paper highlighted a previously unexplored strategy for a biocompatible ionic conductive hydrogel ECP with an excellent MI repair function. Graphical abstract: Herein, a tunable self-healing conductive hydrogel POG1 composed of dynamic network was developed. The microscopic ultra-homogeneous conductive PAA nano-channel existed in the POG1 hydrogel endows the hydrogel with the high stable conductivity under various conditions. The POG1 derived cardiac patch can organize the cardiomyocytes in a certain pattern in vitro and sustain long-time repair effects for myocardial infarction in vivo . Image 1